Co-producing energy futures: impacts of participatory modelling. Issue 7 (2nd October 2016) - Krzywoszynska, Anna; Buckley, Alastair; Birch, Huw; Watson, Matt; Chiles, Prue; Mawyin, Jose; Holmes, Helen; Gregson, Nicky
Abstract : This transdisciplinary research case study sought to disrupt the usual ways public participation shapes future energy systems. An interdisciplinary group of academics and a self-assembling public of a North English town co-produced 'bottom-up' visions for a future local energy system by emphasizing local values, aspirations and desires around energy futures. The effects of participatory modelling are considered as part of a community visioning process on participants' social learning and social capital. This paper examines both the within-process dynamics related to models and the impact of the outside process, political use of the models by the participants. Both a numerical model (to explore local electricity generation and demand) and a physical scale model of the town were developed to explore various aspects of participants' visions. The case study shows that collaborative visioning of local energy systems can enhance social learning and social capital of communities. However, the effect of participatory modelling on these benefits is less clear. Tensions arise between 'inspiring' and 'empowering' role of visions. It is argued that the situatedness of the visioning processes needs to be recognized and integrated within broader aspects of governance and power relations.